Pengaruh Pembayaran Non Tunai dan Tingkat Suku Bunga Kebijakan Terhadap Sistem Pembayaran di Indonesia - Wahyuril Ramadhani; Ris Yuwono Yudo Nugroho (Journal of Business & Banking, 2021)
This study aims to analyze the effect of non-cash payments and policy interest rates on the demand for money in Indonesia in the long and short term. The analysis method used is the Error Correction Model (ECM) with secondary data including electronic money, Card-Based Payment Instruments, BI-RTGS, SKNBI, policy interest rates and M2. The results showed that in the long run, electronic money and APMK had a positive and significant effect on the demand for money. SKNBI and BI-RTGS had a negative and significant effect on demand for money. “In the short term, APMK has a positive and significant effect on money demand. E-Money, SKNBI and BI-RTGS both have positive and insignificant effects on money demand. Policy interest rates have a negative and insignificant effect on money demand in the long and short term. The implication of this research is that in the future there will be more and more people transacting non-cash because it is considered safer, easier and faster. In addition, the demand for base money is reduced which in turn can affect the implementation of the central bank's duties in implementing monetary policy, especially controlling monetary amounts. The development of information technology will have implications for the reduced role of base money in payment transactions.